Development of Human Resource Management Activities in Vietnamese Private Companies (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Human resource management is the coordination of activities to find, develop,maintain, manage and facilitate human resources to operate through the organization, in orderto achieve the goals and direction of the organization. The important requirements of humanresource management is to find the right people, in the right quantity and at the right timewith conditions that satisfy both the business and the applicant. When choosing the rightcandidate for the right position, both individual and business benefit. Human resourcemanagement plays an essential role in the existence and development of enterprises. This isreflected in the factors that help a business operate well or not, succeed or fail, thanks to thepeople who are working at the enterprise with creativity, passion and love. Humans areinvaluable assets for businesses, as technical machines and material possessions can bebought and copied, but people cannot.